Combining Stress Management With Pain Neuroscience Education and Exercise Therapy in People With Whiplash-Associated Disorders: A Clinical Perspective. Issue 7 (24th March 2021) - Willaert, Ward; Leysen, Laurence; Lenoir, Dorine; Meeus, Mira; Cagnie, Barbara; Nijs, Jo; Sterling, Michele; Coppieters, Iris
Abstract: Individuals classified as having whiplash-associated disorder (WAD) grade II, which reflects approximately 93% of people with WAD who are commonly managed by health care professionals, exhibit both physical (eg, pain and disability) and psychological (eg, fear of movement, anxiety, posttraumatic stress) problems that, in approximately 50% of cases, persist beyond 3 months. There is still much ongoing debate regarding factors predictive of poor recovery. The strongest associations have been found for high initial pain and disability following whiplash injury. In addition, a growing body of evidence supports the clinical importance of characteristic features, such as disturbed nociceptive processing (eg, local or general hyperalgesia to cold and mechanical stimuli), inefficient cognitions and beliefs about pain/movement/recovery, and posttraumatic stress symptoms, in the development and maintenance of physical and psychological manifestations in individuals with WAD. For this reason, the field shifted away from single interventions that mainly follow a biomedical approach, such as exercise therapy and activity programs, to gold standard multimodal care (at least 2 distinct therapeutic modalities given by 1 or more health care professionals) that acknowledges the biopsychological nature of WAD. To date, there exist several multimodal care approaches to managing WAD; however, for most, the efficacy has been found to be rather limited. One may argue that the limited success of some approaches can be attributed to the fact that they focused mainly on rehabilitating the physical symptoms (eg, pain, disability) rather than also the associated cognitive (eg, catastrophizing) and psychological (eg, posttraumatic stress symptoms) symptoms of the condition, leaving much room for improvement. In this article, current and previous evidence is used to explain why and how a comprehensive and multimodal treatment for people with WAD—consisting of a combination of pain neuroscience education, cognition-targeted exercise therapy, and stress management—can be applied in clinical practice.